(untitled) (Conferencea, 2023)
In this article, based on the shortcomings of the field and the innovations in the formation of leasing and rental relations, we have taken a broader approach to this topic. In order to improve leasing and rental transactions in Uzbekistan, we approached this topic in a broader way, based on its shortcomings in this field and the news that will be given to it. But before we look at this issue, we will touch on these concepts to have a little idea about leasing and renting.